Mycetoma caused by Trichosporon asteroids-report of the first case - Belda, Walter; Gimenes, Viviane M. F.; Passero, Luiz F. (International Journal of Research in Medical Sciences, 2023)
Mycetoma is a neglected disease that affects mainly the skin, but can progress to deep tissues and structures such as muscles and bones. Mycetoma can be caused by some bacterial (actinomycetoma) or fungal species (eumycetoma); furthermore, eumycetoma is estimated to account for 40% of all cases of mycetomas. Regardless of etiology, human infections occur after accidental implantation of etiological agents through the skin. In the present work, an immunocompetent patient without systemic comorbidity is reported to have exhibited a progressive increase of the left foot with multiple fistulas in the dorsum in the last 15 years, which emerged as a purulent secretion in the presence of yellowish grains. The patient reported that during a trip she suffered injuries in the affected foot. Histopathological study showed the presence of fungal grains, and the culture of skin fragments allowed the identification of fungal colonies exhibiting a dry, cream-coloured cerebriform morphology with a radiated peripheral edge. The micromorphology examination of the isolate demonstrated the presence of hyphae that swell and become multiseptate, budding cells, and lateral conidia were absent. MALD-TOF MS analysis led to the identification of Trichosporon asteroides as etiologic. Different treatment regimens were performed with no success, moderate improvement was observed with voriconazole, and treatment is still ongoing. This is the first case report to incriminate T. asteroides as an etiological agent of eumycetoma.